Factors influencing implementation of Quality Management Systems in meat processing industry in Albania using Ordinal Logistic Regression (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
Objective of this research is to investigate how two attitudes of meat processing enterprises in Albania; ˜Willingness to invest on ISO and ˜Perception about competition level are affected by different factors belonging to internal and external environment of the organization. Stratified random sampling was used for selecting the sample of 45 meat processing enterprises out of 54 officially registered. Face to face interview survey method was conducted. The respondents were mainly managers, owners or high level personnel of the selected meat enterprises. The model of ordinal logistic regression was used to quantify the effects of different management factors on Willingness to invest on ISO and ˜Perception about competition. As result we conclude that the more information and knowledge enterprises have about ISO standards, the more they will have the willingness to invest on these standards. The next finding is that, if companies want to operate in national markets (high competition level) it is a good choice to do a benchmark analysis, also if enterprises in meat industry want to operate in high competitive markets the have to focus on after sales services and on product delivery.